Co‐delivery of microRNA‐21 antisense oligonucleotides and gemcitabine using nanomedicine for pancreatic cancer therapy. Issue 7 (13th June 2017) - Li, Yaqing; Chen, Yinting; Li, Jiajia; Zhang, Zuoquan; Huang, Chumei; Lian, Guoda; Yang, Kege; Chen, Shaojie; Lin, Ying; Wang, Lingyun; Huang, Kaihong; Zeng, Linjuan
Abstract : Tumor metastasis occurs naturally in pancreatic cancer, and the efficacy of chemotherapy is usually poor. Precision medicine, combining downregulation of target genes with chemotherapy drugs, is expected to improve therapeutic effects. Therefore, we developed a combined therapy of microRNA‐21 antisense oligonucleotides (ASO‐miR‐21) and gemcitabine (Gem) using a targeted co‐delivery nanoparticle (NP) carrier and investigated the synergistic inhibitory effects on pancreatic cancer cells metastasis and growth. Polyethylene glycol–polyethylenimine–magnetic iron oxide NPs were used to co‐deliver ASO‐miR‐21 and Gem. An anti‐CD44v6 single‐chain variable fragment (scFvCD 44v6 ) was used to coat the particles to obtain active and targeted delivery. Our results showed that the downregulation of the oncogenic miR‐21 by ASO resulted in upregulation of the tumor‐suppressor genes PDCD4 and PTEN and the suppression of epithelial–mesenchymal transition, which inhibited the proliferation and induced the clonal formation, migration, and invasion of pancreatic cancer cells in vitro . The co‐delivery of ASO‐miR‐21 and Gem induced more cell apoptosis and inhibited the growth of pancreatic cancer cells to a greater extent than single ASO‐miR‐21 or Gem treatment in vitro . In animal tests, more scFvCD 44v6 ‐PEG‐polyethylenimine/ASO‐magnetic iron oxide NP/Gem accumulated at the tumor site than non‐targeted NPs and induced a potent inhibition of tumor proliferation and metastasis. Magnetic resonance imaging was used to observed tumor homing of NPs. These results imply that the combination of miR‐21 gene silencing and Gem therapy using an scFv‐functionalized NP carrier exerted synergistic antitumor effects on pancreatic cancer cells, which is a promising strategy for pancreatic cancer therapy. Abstract : We developed a combined therapy of microRNA‐21 antisense oligonucleotides and Gemcitabine using a targeted co‐delivery nanoparticle carrier and investigated the synergistic inhibitory effects on pancreatic cancer cells metastasis and growth. The synergistic anti‐tumour effects of the combination was observed both in vitro and in vivo, and MR imaging was used to observe tumor homing of nanoparticles.